Zwischen dem Text und seinem Bild. Der Roman "Dr No" von Ian Fleming und seine Verfilmung (Englisch, Deutsch, Polnisch) = Between the text and its picture. The novel "Dr No" by Ian Fleming and its Adaptations - Fimiak-Chwiłkowska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Literary translation is a multidimensional and complex process that gains a new dimension whenthe literary text is transferred onto the screen. This kind of transfer to another medium demandscertain reductions, omissions and simplifications of some elements of the original text, includinga strong visualization. These reflections aim to investigate, on the background of intermediality, thereferences between textuality and figurativeness.
Keywords: Fleming, Ian Lancaster (1908-1964); adaptacja filmowa